UPAYA MENINGKATKAN KETERAMPILAN BERPIKIR PADA MATA KULIAH MATEMATIKA DENGAN PEMBERDAYAAN BERPIKIR MELALUI PERTANYAAN (PBMP) BAGI MAHASISWA UT POKJAR NGAWI - Tresnaningsih, Sri (JURNAL AGRI-TEK, 2018)
Open University as one of State Universities since the beginning has done different lectures with regular colleges. In Distance Learning Higher Education (PTTJJ) students are required to study independently. Self-learning requires students to learn on their own initiative or initiative. Self-study can be done independently or in groups, either in study groups or in tutorial groups. Self-study will support a learning paradigm centered on Student Center Learning (SCL) students, is not teacher-centered Teacher Center Learning (TCL) teaching. Student-centered learning feels more empowering thinking skills and can construct knowledge. Learning through questioning is one way that can be empowered so that students can construct knowledge. Learning through questioning is one way that can be empowered so that students can construct knowledge. There are several strategies, methods, or models of learning through asking. PBMP (Empowerment of Thinking Through Questions) or TEQ (Thinking Empowerment by Questioning). Mathematics Course (PDGK 4108) consists of 12 modules How tutors can deceive students thinking through questions, so that face-to-face tutorials as much as 8 times can be optimal. Keywords: thinking skills, mathematics, PBMP.